Tingkat Erosi pada Plot Model Arsitektur Pohon Attims (Eucalyptus deglupta), Corner (Arenga pinnata), dan Rauh (Arthocarpus teysmanii) - Naharuddin Naharuddin (Fakultas Kehutanan Universitas Gadjah Mada, 2021)
Tree architecture models and the composition of vegetation types affected surface runoff and erosion rates due to vegetation density and various other morphological and ecological characteristic components. This research purpose was to measure and compare the level of erosion in 3 tree architectural models. The research used the path plots method. The sample pathway was made by cut off contour lines. To measure the erosion rate that occured at the tree architecture model, erosion measuring plots were used in three tree architecture models, namely Attims (Eucalyptus deglupta), Corner (Arenga pinnata), and Rauh (Arthocarpus teysmanii). The results showed that the dominant tree architecture model was the Rauh, Attims, and Corner models. The erosion level which occurred in the three tree architectural models showed that the Attims Eucalyptus deglupta model and Corner Arenga pinnata models were more effective in controlling erosion by 233.55 g/ha/year and 293.10 g/ha/year with rainfall of 493.55 mm compared to Rauh Arthocarpus teysmanii type. The correlation analysis between rainfall and the erosion rate at the three tree architecture models were 80% (very strong) for Attims model, 89% (very strong) for Corner model and 90% (very strong) for Rauh model. To control the erosion the Attims and Corner models are highly recommended as alternatives for rehabilitating the critical land.